ACTIVE CYCLE OF BREATHING TECHNIQUE (ACBT) AGAINST PEAK EXPIRATORY FLOW IN COPD PATIENTS - Yuniarti, Enny Virda (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
COPD patients often experience the accumulation of secretions in the respiratory tract. To overcome the buildup of secretions in the respiratory tract, the Active Cycle Of Breathing Technique (ACBT) can be applied to the respiratory tract and increase the value of peak expiratory flow. This study aims to determine the effect of active cycle of breathing technique therapy (ACBT) therapy on peak expiratory flow in COPD patients. This research is a Pre-experimental type research that uses a One Group Pretest-Posttest design with the provision of ACBT intervention done 1x on the respondent. Instruments in evaluating lung function lung function of this study using the Peak Flow Meter. The sample in this study amounted to 30 respondents who had been selected through purposive sampling based on inclusion and exclusion criteria by researchers. Data analysis technique data in this study using the Paired T-Test test with the help of the SPSS program. Before being given ACBT intervention, the average value of peak respiration flow was found to be 83.67 lpm and after the ACBT intervention, the average value of peak flow of respiration was found to be 185.00 lpm. The results of statistical test analysis using Paired T-test obtained the results of p-value obtained 0.000 < α0.05 then there is a difference in the average value of peak expiratory flow before and after ACBT in patients with Chronic Obstructive Pulmonary Disease. This study concludes that there is a significant effect of the application of the Active Cycle of Breathing Technique (ACBT) intervention on the value of peak respiration flow in COPD patients.